Pulse shaping, high average power narrow linewidth Er, Yb co-doped fiber amplifier - Wang, Yunpeng; Li, Yang; Zhang, Dongming; Xiong, Chen; Li, Pingxue (Frontiers in Physics, 2023)
We demonstrate a high repetition rate, high average power narrow-linewidth fiber amplifier at 1.55 μm eye-safe waveband by using a very-large-mode-area active fiber doping Er and Yb, having a 60-μmdiameter core and a 600-μm-diameter inner cladding. A maximum average power reaches 16 W at a 10 kHz repetition rate for 600 ns pulses in the stimulated Brillouin scattering (SBS) free operation, which calculates to a 1.6 mJ pulse energy and 2.7 kW peak power. In addition, the peak power rises to 4.9 kW with 148 ns pulses at the onset of SBS. The signal peak is located at 1551.15 nm with a 36 dB signal-to-noise ratio (SNR). In order to eliminate the pulse steepening, the pulse shaping technology using a triangular-like wave with a slower rising edge is applied on the input pulses. The half-width of the frequency-intensity spectrum from high-average-power fiber amplifier is about 1.02 MHz, approaching the Fourier transform limit.